MARRIAGE CONCEPTS AND ESSENCE FROM THE PERSPECTIVE OF CLASSICAL ISLAMIC JURISPRUDENCE AND INDONESIAN NATIONAL LAW - Mukhlis Tri Mulya Marpaung; Muhammad Amar Adly (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2026)
Marriage is a legal institution that occupies a central position in both Islamic family law and Indonesian national law. However, public understanding of the nature of marriage is often reduced to mere formality, obscuring its substantive and spiritual significance. This study aims to analyze the concept of marriage (nikah) in classical fiqh, to understand the essence of marriage as both a legal contract (aqd) and a solemn covenant (mitsaqan ghalizhan), and to examine the regulation of marriage within the Indonesian national legal system. This study employs normative legal research with a conceptual approach and comparative approach. Primary legal materials include the Qur'an, Hadith, Law Number 1 of 1974 as amended by Law Number 16 of 2019 on Marriage, and the Islamic Law Compilation (KHI), while secondary materials consist of classical fiqh texts and contemporary scientific literature. Data analysis employs descriptive-analytical and comparative methods. The findings reveal that: first, classical fiqh scholars define marriage in varied ways yet converge on one substance, with the legal status being dynamic according to individual circumstances (obligatory, recommended, permissible, discouraged, or prohibited); second, marriage in Islam integrates two complementary dimensions, namely the contractual dimension as a formal legal framework and the mitsaqan ghalizhan dimension as a moral-spiritual framework; and third, the Indonesian national legal system accommodates Islamic fiqh values through the Marriage Law and KHI, with the obligation of registration serving as an instrument for protecting citizens' rights in harmony with maqasid al-shari'ah.Keyword: Islamic Marriage; Classical Fiqh; Mitsaqan Ghalizhan; National Law